composition of cotyledons and primary roots of Citrullus vulgaris seeds when germinated at 30°C in the dark. The studies at different stages of germination help to understand the biosynthesis of lipids and the natural pathway of the formation of fatty aci (Biological Sciences - PJSIR, 2022)
The lipid content of primary roots (10, 20, and 30 mm)and the respective cotyledons were determined according toFolch's method [7,8] (Table I) and the lipids were classifiedinto neutral and polar lipids by TLC [9,10] using differentsolvent systems (Table 2).